Prevalence and Antibiotic Susceptibility of Proteus mirabilis Isolated from Clinical Specimens in the Zainoel Abidin General Hospital, Banda Aceh, Indonesia - Suhartono, Suhartono; Mahdani, Wilda; Khalizazia, Khalizazia (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Proteus mirabilis is Gram-negative bacteria from the Enterobacteriaceae family causing various infections. AIM: This study aimed to determine the prevalence and distribution of Proteus mirabilis isolated from clinical specimens based on patients’ age, gender, type of specimen, and patient wards and their antibiotic sensitivity. METHODS: This study involved isolating, identifying, and testing antibiotic susceptibility to Proteus mirabilis isolates recoverred from clinical specimens of dr. Zainoel Abidin general hospital Banda Aceh during March 2020-March 2022. RESULTS: This study showed that 121 isolates of Proteus mirabilis were obtained from clinical specimens during the study with prevalence of almost 2%. Proteus mirabilis distribution based on the specimen type was most predominantly found in pus specimens and from patients in the the operating room and post surgery ward accounting for 84.29% and 35.53%. Proteus mirabilis was detected most frequently in individuals aged 46-55 years old (30.57 %), whereas it was found more frequently in men (71%) based on gender. The susceptibility of Proteus mirabilis to antibiotics was highest to cefoperazone, piperacillin/tazobactam, and amikacin reaching reaching 97.5%, 97.5, and 96.66%, respectively. CONCLUSION: The distribution of Proteus mirabilis isolates predominantly in pus specimens indicating its association with wound infections. Despite some antibiotics remain effective, implementation of the regular surveillance programs along with rational use of antibiotics may prevent the bacterial pathogen to spread particularly within healthcare settings.